Impacts of Coal Stockpile on Soil and Water - A. K. M. Al-Amin; Md. Shahriar Azam; Md. Shazzadur Rahman; Afifa Tajremin; M. K. Haque; Tahmina Akter Rimi (Archives of Current Research International, 2019)
In this study, the soil and water samples were analyzed to evaluate the effects of coal stockpile on soil and water quality at Haluaghat Upazilla, Mymensingh, Bangladesh. As a natural resource, coal has potential contributions to the development of economics of a country but coal storage deteriorates surrounding surface and ground water and soil quality in different ways. Besides, it has significant impacts on the arable lands and water catchments. The analyses of 10 soil and 10 water samples (5 samples from ground water and 5 samples from surface water) were collected at 0 m, 200 m, 500 m and 700 m distance from the coal storage area were carried out using standard methods. The pH, electrical conductivity (EC), organic matter (OM), macronutrients (N, P and K) and heavy metals (Lead and Cadmium) were analysed for soil samples and for water samples pH, EC, macronutrients (P and K), heavy metals (Pb and Cd) were analysed. From the results, it was observed that most of the value of soil and water quality components were higher at close to the coal stockpile area and gradually decreased with distance. Soil pH value showed a decreasing trend (5.2 to 3.2) with increasing distances from the coal storage area; whereas water pH increased gradually with increasing distances from the coal storage area. Soil OM content was found highest at the coal storage area, which decreased gradually with increasing distance. The content of soil N, P, K was also recorded highest at the coal storage area which followed decreasing trend with increasing distance. The content of Pb and Cd in soil adjacent to coal storage area was higher compared to distant areas (500-700 m) in paddy field. The soil quality might be deteriorated due to coal stockpile effluents. The effluents from the coal stockpile should be treated before it is discharged to soil or water.